Estudo herdabilidade de alguns caracteres em pessegueiro: ciclo, tonalidade da cor da polpa e compostos fenólicos - Corrêa, Elisia Rodrigues (2007)
The knowledge of the genetic, phenotypic and environmental parameters of peach characteristics is of fundamental importance in breeding programs, because it allows to foresee the possibility of success with the selection. The present work had as objectives to estimete the heritability, in broad of the fruit development period (FDP), flesh color intensity and total phenolics as well as determining possible correlations of the last with the other two mentioned characters. The studied populations originated from the Peach Genetic Breeding Program of Embrapa Clima Temperado. For the FDP study 196 individuals belonging to five progenies program crosses of year 2000, were observed (two originating from the second generation and the others, first generation). Seedlings of 14 progenies resulting from crosses among 12 peach cultivars and six selections were used in the evaluations. Six of these progenies were F1 generation and the others, F2 (second generation), obtatained by opened pollination. The dear value of the herdabilidade in the wide sense went loud to the cycle, low for the flesh and medium for the total phenolics (H=0,90; H=0,25; H=0,46 respectively). These values indicate that for the character cycle is possible to have won of selection while for the pulp no, for also having influence of environmental factors what a little